Perfection of the mechanism of planning of innovative activities based on the system-transdisciplinary approach - P. M. Gureev; V. N. Grishin; E. N. Dunenkova; S. I. Onishchenko (Управление)
The possibility of applying transdisciplinary system methodology in the process of developing plans for the innovative development of business entities has been considered. The use of a transdisciplinary systematic approach to innovation planning allows you to use new methodological planning tools, strengthen the systematic nature of planned activities, more clearly define their content and sequence.Various variants of the classification of scientific approaches according to the criterion of the degree of completeness of cognition of the surrounding world have been analysed, the basic transdisciplinary methodological approaches according to the content criteria and possibilities have been compared, such as: the theory of autopoiesis, the theory of chaos and complexity, the theory of fractals, the theory of turbulence and the theory of economic genetics.An important factor in the proposed methodology is the use of the evolutionary property of the development of organizational systems in combination with the possibility of revolutionary transformations at certain stages of development that determine the susceptibility of the organizational system to innovations. In the process of planning innovations, it is only possible to take into account these features of the development of organizational systems using a systemic transdisciplinary methodology.In the process of research, a transdisciplinary tool such as multiplex has been proposed for use, allowing us to determine the duration of the “internal” periods of development of the organizational system and, consequently, increase the validity of planned measures for the implementation of innovations. The use of this tool in the planning process has allowed us to find an approach to determining the duration of the periods of the various stages of the innovation process, which can in future provide an opportunity to effectively distribute the resources of an economic entity over time. At the same time, special attention in the process of planning investments in the innovation process has been paid to the practice of venture and business angel financing, the positive performance of which has been proved by the example of the United States.